Prevalence and predictors of postcholecystectomy syndrome in Nepalese patients after 1 week of laparoscopic cholecystectomy: a cross-sectional study - Roshani Shrestha; Prangtip Chayaput; Kessiri Wongkongkam; Wallada Chanruangvanich (Scientific Reports, 2024)
Abstract Postcholecystectomy syndrome (PCS) is persistent distressing symptoms which develops following a laparoscopic cholecystectomy (LC); in cases when the condition is severe, readmission may be necessary. However, research on the prevalence of PCS and potential factors associated with PCS in Nepalese patients is still limited. An observational point-prevalence, correlational predictive cross-sectional study was conducted to determine the prevalence of PCS and examine what predicting factors including preoperative anxiety, preoperative dyspepsia, smoking, alcohol consumption, and duration of preoperative symptoms are associated with PCS. A total of 127 eligible Nepalese patients who came for follow-up after 1 week of LC at outpatient department of surgery in one single university hospital, Kathmandu, Nepal, were recruited. A set of questionnaires consisting participants' information record form, Hospital Anxiety and Depression Scale (HADS), Leeds Dyspepsia Questionnaires (LDQ), Fagerstrom Test for Nicotine Dependence (FTND), and Alcohol Use Disorder Identification Test (AUDIT) was administered for data collection. The associations between influential factors and PCS were analyzed using Binary logistic regression. 43.3% of participants reported PCS after 1 week of surgery. The findings from logistic regression analysis affirmed that the patients with preoperative anxiety (OR = 6.38, 95%CI = 2.07–19.67, p < 0.01) and moderate to severe dyspepsia (OR = 4.01, 95%CI = 1.34–12.02, p < 0.05) held the likelihood to report PCS 6.38 and 4.01 times, respectively, greater than others. The implications from study results are that screening of anxiety and patients’ tailored interventions to reduce anxiety should be implemented preoperatively. An appropriate health education about persistence of PCS and self-management should be provided to those postoperative patients.